α-Sulfonyl radical initiated intramolecular tandem radical cyclization - Vichai Reutrakul (2018)
Suitable derivatives of hex-5-enyl α-sulfonyl radical undergo cyclization to produce complex cyclic systems by a multiple radical chain mechanism. © 1989.